2023
DOI: 10.1080/20008066.2023.2179278
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of white matter structural connectivity in healthy adults with childhood maltreatment

Abstract: Background: Childhood maltreatment (CM) is a common psychological stressor associated with multiple mental disorders. While CM is associated with vulnerability to depression and anxiety, little is known about the specific mechanism underlying this relationship. Objective: This study aimed to investigate the white matter (WM) of healthy adults with CM and their relationships with depression and anxiety to provide biological evidence for the development of mental disorders in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2024
2024
2025
2025

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
0
2
1
Order By: Relevance
“…This might indicate that the reduction in FA in the right IFOF and PLIC might be a specific change in the WM regions of MDD patients, independent of CT. These results differ from previous studies related to CT ( 15 17 , 34 , 35 ). However, Lim et al.’s study found that specific WM changes in the CT group were rectified in the subgroup analysis of unmedicated participants ( 34 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This might indicate that the reduction in FA in the right IFOF and PLIC might be a specific change in the WM regions of MDD patients, independent of CT. These results differ from previous studies related to CT ( 15 17 , 34 , 35 ). However, Lim et al.’s study found that specific WM changes in the CT group were rectified in the subgroup analysis of unmedicated participants ( 34 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Studies involving gray matter regions have found an association between CT experience and lower volumes of the hippocampus and amygdala ( 12 14 ). Beyond gray matter regions, several studies have reported specific white matter(WM) changes in individuals with an experience of CT, including the inferior longitudinal fasciculus, uncinate fasciculus, thalamic radiation, corona radiata, longitudinal fasciculi, cingulum, and corpus callosum ( 15 17 ). Notably, there is an anatomical overlap between the specific WM change areas in MDD patients and those mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…The degeneration of white matter fiber has been associated with cognitive impairment and poor prognosis in stroke survivors ( 5 , 24 ). Childhood maltreatment can alter the microstructure of white matter in healthy adults, which might increase their vulnerability to mental disorders such as anxiety and posttraumatic stress disorder ( 25 , 26 ). Poor sleep quality might lead to neural injury by damaging the white matter microstructure, and this knowledge may provide guidance for decision-making in precision medicine ( 27 ).…”
Section: Discussionmentioning
confidence: 99%